Physico-chemical quality of drinking water of Mpohor, Mpohor-Fiase District of the Western Region, Ghana - Bedu- Mensah, Henry (2015)
A thesis Submitted to the Department of Theoretical and Applied Biology, College of Science, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the degree of Master of Science (Environmental Science),2014